Direct Oral Anticoagulants in Patients With Atrial Fibrillation and Advanced Liver Disease: An Exploratory Meta‐Analysis. Issue 7 (7th May 2020) - Violi, Francesco; Vestri, Annarita; Menichelli, Danilo; Di Rocco, Arianna; Pastori, Daniele; Pignatelli, Pasquale
Abstract : Direct oral anticoagulants (DOACs) have had a positive impact in preventing cardioembolic stroke in patients with atrial fibrillation (AF) who were associated with lower bleeding complications; however, data on subjects with concomitant advanced liver diseases (ALDs) are poor. This meta‐analysis evaluates bleeding and thromboembolic complications in patients with coexisting AF and ALD who were treated with DOACs or vitamin K antagonists (VKAs). We performed a meta‐analysis of randomized controlled trials and observational studies identified by the PubMed and Embase databases using a combination of the following keywords: "direct oral anticoagulants, " "advanced liver disease, " "cirrhosis, " "bleeds, " "stroke." No time restriction was applied to the research. Two physicians reviewed data on outcome measures and assessed the quality rating. The main outcome was major bleeding, and the secondary outcomes were bleedings (all, intracranial, and gastrointestinal) and ischemic strokes. A total of four studies (one prospective, three retrospective) were identified involving 3, 483 subjects with AF and ALD; of these, 1, 547 were on VKAs and 1, 936 on DOACs. Advanced liver disease was defined as liver cirrhosis or fibrosis‐4 score >3.25. Compared to VKA use, DOAC use was associated with reduced risk for major bleedings (hazard ratio [HR], 0.58; 95% confidence interval [CI], 0.44‐0.77; P  < 0.001), total bleedings (HR, 0.45; 95% CI, 0.36‐0.55; P  < 0.05), intracranial hemorrhage (HR, 0.51; 95% CI, 0.32‐0.80; P  < 0.004), and gastrointestinal bleedings (HR, 0.61; 95% CI, 0.42‐0.88; P  < 0.008). Efficacy analysis showed no significant difference between VKA‐ and DOAC‐treated patients (HR, 0.83; 95% CI, 0.58‐1.15; P  = 0.31). Conclusion: In patients with AF and ALD, the safety and efficacy profile of DOACs did not appear to differ from those with AF without ALD.